Strategy for Developing Agribusiness Partnership Patterns of Farmer Groups at the Agricultural Extension Center (BPP) of East Dumai District, Dumai City - Fara Shaliza; Hildawati Hildawati; Egi Miranda Yuri; Fanisa Fanisa (FUNDAMENTUM : Jurnal Pengabdian Multidisiplin, 2023)
This community service program was motivated by the suboptimal development of agribusiness partnership patterns among farmer groups assisted by the Agricultural Extension Center (BPP) of East Dumai District, Dumai City, which has resulted in low productivity, limited value added, and weak bargaining power of farmers. The program aimed to enhance farmers’ understanding, capacity, and readiness to develop sustainable agribusiness partnership strategies. The method applied was a community organizing approach through counseling, participatory discussions, and mentoring involving five farmer groups with a total of 15 farmers. The results indicate an improvement in farmers’ understanding of agribusiness partnership concepts and models, a shift in mindset from individual to collective group-based farming, and the emergence of initial agreements to develop simple partnership schemes with local agribusiness actors. In addition, farmers showed increased readiness in managerial aspects, product quality improvement, and communication with potential partners. This program contributes to strengthening farmer group institutions and provides a foundation for developing more structured and sustainable agribusiness partnerships.